Enteric coated microspheres of pancreatin in the treatment of cystic fibrosis: comparison with a standard enteric coated preparation. Issue 7 (July 1987) - Stead, R J; Skypala, I; Hodson, M E; Batten, J C
Abstract : In an open, randomised crossover study enteric coated microspheres of pancreatin were compared with a standard preparation of enteric coated pancreatin over two consecutive 28 day treatment periods in 23 adults with steatorrhoea due to cystic fibrosis. Lipase intake was equal to the patients' previous requirements and was the same during the two months. Patients performed 72 hour faecal collections at the end of each month and completed diary cards daily throughout. Comparison of the month of treatment with enteric coated microspheres with the month of standard enteric coated tablets showed a significant increase in body weight on microsphere capsules (p less than 0.02). There was also a reduced frequency of bowel actions (p less than 0.001) and abdominal pain (p less than 0.05), and improvement in stool character (p less than 0.001) on microsphere capsules. Faecal fat excretion was reduced by 44% with the microsphere capsules (p less than 0.01), and 86% of patients showed an increased coefficient of fat absorption (mean increase 13%, 95% confidence limits 6.5-19.1%; p less than 0.001). Eighty one per cent of patients preferred microsphere capsules of the two treatments. Thus enteric coated microsphere capsules are more effective in treating steatorrhoea in cystic fibrosis than standard enteric coated tablets.